1982
DOI: 10.1068/p110663
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Paradigm for Conditioning Visual Perception in Human Subjects

Abstract: Repeated pairing of an auditory conditioned stimulus with a weak visual unconditioned stimulus produced extended image sequences and visual responses conditioned to the tone alone. The experiment is set into the context of Pavlov's view of Helmholtz's "unconscious inference" thus providing experimental evidence linking the higher mental process of perception with classical conditioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Pavlov equated the learned conditioned reflexes that he observed with Helmholtz' learned perceptual expectancies (Barlow, 1990;Helmholtz, 1878Helmholtz, /1971, an assertion supported by empirical evidence (Davies et al, 1982). Such conditioned expectancies are also important for causal inference and belief formation (Dickinson, 2001); in particular, we learn most in situations that violate our expectancies, inducing prediction error (Rescorla and Wagner, 1972); we attend most to features that are coincident with prediction error (Pearce and Hall, 1980) and we use prediction errors to learn the parameters of causal models as well as which causal models are able to explain the co-occurrence of particular events (Waldmann and Martignon, 1998).…”
Section: Pðhjdþ ¼ Pðdjhþpðhþ Pðdþmentioning
confidence: 53%
“…Pavlov equated the learned conditioned reflexes that he observed with Helmholtz' learned perceptual expectancies (Barlow, 1990;Helmholtz, 1878Helmholtz, /1971, an assertion supported by empirical evidence (Davies et al, 1982). Such conditioned expectancies are also important for causal inference and belief formation (Dickinson, 2001); in particular, we learn most in situations that violate our expectancies, inducing prediction error (Rescorla and Wagner, 1972); we attend most to features that are coincident with prediction error (Pearce and Hall, 1980) and we use prediction errors to learn the parameters of causal models as well as which causal models are able to explain the co-occurrence of particular events (Waldmann and Martignon, 1998).…”
Section: Pðhjdþ ¼ Pðdjhþpðhþ Pðdþmentioning
confidence: 53%
“…Y Conditioned afterimages. It has been reported that visual experiences (in the absence of visual input) can be elicited as conditioned responses to tones after pairing images with tones (49). This finding would demonstrate a conditioned visual response but not one that occurs during normal vision.…”
Section: Discussionmentioning
confidence: 74%
“…Pavlov believed that one could equate his conditioned reflexes with Helmholtz' learned perceptual expectancies (Barlow, 1990; Helmholtz, 1871/1971), an assertion supported by empirical evidence (Davies et al, 1982). Recently, computational neuroscientists have also come to appreciate the overlap between learning and perception, emphasizing the consilience between formal theories of conditioning, Bayesian accounts of learning and signal detection theories of perceptual decision making (Dayan and Daw, 2008).…”
Section: Internal Reinforcement Hypothesis and Delusionsmentioning
confidence: 97%